THE AGENDA OF PANCASILA LEADERSHIP ON EDUCATION SECTOR IN OVERCOMING CORRUPTION - Leo B. Barus; Elvrida N. Sinaga (Scientia Integritas Utama, 2022)
The rampant corruption in several sectors, including the education sector, has raised question due to what is lacking in Law Number 20 of 2003 concerning the National Education System which has mandated that national education is always rooted in religious values, national culture, and responsive to demands of changing times. It is necessary to consider instilling the Pancasila character in Indonesian schools. It is concluded that corruption that still occurs in Indonesia must be dealt with through the cultivation of the Pancasila Leadership character according to the level of education. It is suggested that in the future, leadership in the education sector, for example class heads, student council heads, and scout leaders, have passed the talent management selection that has the qualifications of ing ngarso sung tulodo, ing madyo mangun karso, and tut wuri handayani principles. The cultivation of Pancasila leadership must be carried out in various student education activities, including in intra-curricular, co-curricular, extra-curricular activities, and non-co-curricular activities.